High-strength fiber reinforced concrete and method for producing the same
Patent Information
- Application Number
- CN202611229608.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-13
- Publication Date
- 2026-10-16
AI Technical Summary
[0003]然而,传统超高强混凝土通过提高水泥用量、降低水胶比、增加硅灰实现高强度,但水化热高、自收缩大、脆性显著提升,开裂风险剧增
[0033] 1. A low-heat micro-expansion cementitious system combined with a composite crack-resistant agent is used to reduce shrinkage from the source; the internal curing agent releases moisture to promote the secondary hydration of unhydrated cementitious materials, while promoting the expansion reaction of the composite crack-resistant agent. The expansion stress is constrained by the ternary fiber network, forming micro-pre-stress inside the concrete, which greatly offsets the later shrinkage.
Smart Images

Figure CN122916545A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of building materials technology, and in particular to a high-strength fiber-reinforced concrete and its preparation method. Background Technology
[0002] The transition section of a wind turbine hybrid tower, located at the top of the tower, is a core force-transmitting component connecting the upper steel tower and the lower concrete tower. It bears the dynamic loads, fatigue loads, and enormous bending and torques generated by the nacelle and blades over long periods, making it the most stress-intensive and concentrated part of the entire tower. This places far greater demands on the concrete materials than on ordinary tunnel lining segments: it needs to achieve ultra-high strength of C90-C100 grade to ensure structural safety and reduce component cross-sections; simultaneously, it requires extremely high crack resistance and durability to adapt to harsh service environments such as high altitudes and coastal areas.
[0003] However, traditional ultra-high strength concrete achieves high strength by increasing cement content, reducing the water-cement ratio, and adding silica fume, but this results in high heat of hydration, large autogenous shrinkage, significantly increased brittleness, and a dramatically increased risk of cracking. Existing single-fiber reinforcement technologies have limitations: steel fibers are costly, prone to clumping, and affect workability, and have limited effectiveness in suppressing early plastic cracks; synthetic fibers are effective against early plastic shrinkage, but insufficient in controlling load-bearing and structural cracks. Furthermore, the lack of integrated design for ultra-high strength and high crack resistance in cementitious materials, aggregates, fibers, and admixtures easily leads to poor workability, strength fluctuations, and insufficient durability. Existing C90 concrete is mostly general-purpose and has not been optimized for the prefabrication process of transition segments, steam curing, and the timing of prestressing.
[0004] Therefore, how to overcome the technical bottlenecks of existing ultra-high strength concrete, which has high strength, high brittleness, easy cracking, and poor workability, and provide a special concrete for the transition section of wind power hybrid towers that combines ultra-high strength, high crack resistance, and excellent workability, is a technical problem that urgently needs to be solved in this field. Summary of the Invention
[0005] To address the aforementioned shortcomings, a high-strength fiber-reinforced concrete and its preparation method are provided.
[0006] In a first aspect, the present invention provides a high-strength fiber-reinforced concrete, comprising the following components by weight:
[0007] 52.5 grade low-alkali silicate cement: 350-380 parts;
[0008] Silica fume: 25-35 parts;
[0009] S105 grade ultrafine mineral powder: 100-160 parts;
[0010] Ultrafine fly ash or metakaolin: 25-35 parts;
[0011] Crack-resistant agent: 10-20 parts;
[0012] Coarse aggregate: 1000-1100 parts;
[0013] Fine aggregate: 600-680 parts;
[0014] Macroscopic reinforcing fiber: 5-25 parts;
[0015] Microscopic crack-resistant fibers: 3-6 parts;
[0016] Micro-toughening fibers: 0.6-1.2 parts;
[0017] Viscosity-reducing polycarboxylate high-performance water-reducing agent: 11-18 parts;
[0018] Internal conditioner: 1.5-4 parts;
[0019] Water: 90-115 parts;
[0020] The 52.5 grade low-alkali silicate cement, silica fume, S105 grade ultrafine mineral powder, ultrafine fly ash or metakaolin, and the crack-resistant agent together constitute the cementitious material, and the mass ratio of water to the cementitious material is 0.14-0.23.
[0021] Optionally, the crack-resistant agent is a composite crack-resistant agent, a magnesium crack-resistant agent, or a mixture of a composite crack-resistant agent and a magnesium crack-resistant agent; the composite crack-resistant agent is composed of a light-burned magnesium oxide expansion source and a shrinkage-reducing component mixed at a mass ratio of 6:4; the magnesium oxide content of the light-burned magnesium oxide expansion source is ≥95%; and the shrinkage-reducing component is a powder shrinkage-reducing agent.
[0022] Optionally, the coarse aggregate is high-strength granite or basalt crushed stone with a particle size of 5-12mm or 5-16mm, and the content of needle-like and flaky particles in the coarse aggregate is ≤3%, and the crushing index is ≤8%; the fine aggregate is manufactured sand with a methylene blue value (MB) ≤0.8, a stone powder content of 6-9%, and has undergone three-stage gradation optimization.
[0023] Optionally, the macroscopic reinforcing fiber is a hook-shaped or corrugated steel fiber with a length of 30-35 mm and an aspect ratio of 50-70; the microscopic crack-resistant fiber is a polypropylene coarse fiber with a diameter of 0.3-0.5 mm and a length of 18-24 mm; and the microscopic toughening fiber is a high-modulus PE or POM ultrafine fiber with a diameter of 10-50 μm and a length of 6-12 mm.
[0024] Optionally, the water reduction rate of the viscosity-reducing polycarboxylate high-performance water-reducing agent is ≥40%; the internal curing agent is pre-absorbent lightweight aggregate or pre-absorbent saturated superabsorbent polymer (SAP).
[0025] Secondly, the present invention provides a method for preparing high-strength fiber-reinforced concrete, wherein the high-strength fiber-reinforced concrete described in any one of the above-mentioned methods is prepared as follows:
[0026] The micro-toughening fibers are dry-mixed with 40% of the total amount of cementitious materials and all fine aggregates to form a dispersion.
[0027] Add the coarse aggregate, the dispersed material, the macroscopic reinforcing fiber, and the fine crack-resistant fiber to the mixer and dry mix for 60-90 seconds;
[0028] Add the remaining cementitious material and 60% of the total water volume of water, stir for 90 seconds to obtain a slurry;
[0029] Add the remaining water, viscosity-reducing polycarboxylate superplasticizer and internal curing agent, and force stir for ≥240s until the spread of the slurry is ≥650mm;
[0030] The slurry is cast into shape and compacted using either high-frequency, vibration-free or low-frequency, large-amplitude vibration.
[0031] After pouring, initial covering and water retention curing are carried out; after water retention curing is completed, steam curing is carried out, with the temperature increased at 15℃ / h to the maximum temperature, the maximum temperature being ≤60℃, and the temperature is maintained for 6-8 hours, followed by cooling down at 10℃ / h; after demolding, wet curing or sealed curing is carried out for ≥14 days.
[0032] The beneficial effects of this invention are as follows:
[0033] 1. A low-heat micro-expansion cementitious system combined with a composite crack-resistant agent is used to reduce shrinkage from the source; the internal curing agent releases moisture to promote the secondary hydration of unhydrated cementitious materials, while promoting the expansion reaction of the composite crack-resistant agent. The expansion stress is constrained by the ternary fiber network, forming micro-pre-stress inside the concrete, which greatly offsets the later shrinkage.
[0034] 2. A multi-scale hybrid fiber system is formed by using fine polypropylene coarse fibers, micro PE or POM ultrafine fibers, and preferably macro steel fibers, to inhibit crack initiation and propagation throughout the entire cycle and at multiple scales, reducing the early crack area by more than 90%.
[0035] 3. The prepared concrete has a 28-day compressive strength ≥95MPa, a flexural toughness improvement of over 300%, a spread ≥650mm, excellent workability, and a chloride ion diffusion coefficient <1.0× m² / s, meeting the 100-year lifespan design requirements for coastal and high-altitude applications, and the process is compatible with existing prefabrication production lines.
[0036] Thirdly, the present invention provides a wind power hybrid tower transition section, which is prepared using the above-mentioned high-strength fiber concrete preparation method. Attached Figure Description
[0037] Figure 1 This is a schematic flowchart illustrating a method for preparing high-strength fiber-reinforced concrete according to an embodiment of the present invention.
[0038] Figure 2 The diagram shows the damage of the high-strength fiber-reinforced concrete prepared according to an embodiment of the present invention during a compressive strength test.
[0039] Figure 3 This is a compressive failure surface diagram of the high-strength fiber-reinforced concrete prepared according to an embodiment of the present invention;
[0040] Figure 4 A scene diagram showing the splitting crack test of the high-strength fiber-reinforced concrete prepared in an embodiment of the present invention;
[0041] Figure 5 This is a splitting failure surface diagram of the high-strength fiber-reinforced concrete prepared according to an embodiment of the present invention. Detailed Implementation
[0042] The expansion source of light-burned magnesium oxide used in the embodiments of the present invention can be a commercially available product, such as Kaitai Chemical brand light-burned magnesium oxide (magnesium oxide content ≥95%); the shrinkage reducing component can be a commercially available product, such as Shanghai Deweyno brand powder shrinkage reducing agent.
[0043] The technical solution of the present invention will be further described below with reference to the accompanying drawings and embodiments:
[0044] 1. A high-strength fiber-reinforced concrete, comprising the following components by weight:
[0045] 52.5 grade low-alkali silicate cement: 350-380 parts;
[0046] Silica fume: 25-35 parts;
[0047] S105 grade ultrafine mineral powder: 100-160 parts;
[0048] Ultrafine fly ash or metakaolin: 25-35 parts;
[0049] Crack-resistant agent: 10-20 parts;
[0050] Coarse aggregate: 1000-1100 parts;
[0051] Fine aggregate: 600-680 parts;
[0052] Macroscopic reinforcing fiber: 5-25 parts;
[0053] Microscopic crack-resistant fibers: 3-6 parts;
[0054] Micro-toughening fibers: 0.6-1.2 parts;
[0055] Viscosity-reducing polycarboxylate high-performance water-reducing agent: 11-18 parts;
[0056] Internal conditioner: 1.5-4 parts;
[0057] Water: 90-115 parts;
[0058] The cementitious material is composed of 52.5 grade low alkali silicate cement, silica fume, S105 grade ultrafine mineral powder, ultrafine fly ash or metakaolin, and crack-resistant agent. The mass ratio of water to cementitious material is 0.14-0.23.
[0059] Optionally, the crack-resistant agent is a composite crack-resistant agent, a magnesium crack-resistant agent, or a mixture of a composite crack-resistant agent and a magnesium crack-resistant agent. The composite crack-resistant agent is composed of a light-burned magnesium oxide expansion source and a shrinkage-reducing component mixed at a mass ratio of 6:4. The magnesium oxide content of the light-burned magnesium oxide expansion source is ≥95%. The shrinkage-reducing component is a powder shrinkage-reducing agent.
[0060] Optionally, the coarse aggregate is high-strength granite or basalt crushed stone with a particle size of 5-12mm or 5-16mm, the content of needle-like and flaky particles in the coarse aggregate is ≤3%, and the crushing index is ≤8%; the fine aggregate is manufactured sand with a methylene blue value (MB) ≤0.8, a stone powder content of 6-9%, and has undergone three-stage gradation optimization.
[0061] Optionally, the macroscopic reinforcing fiber is a hooked or corrugated steel fiber with a length of 30-35 mm and an aspect ratio of 50-70; the microscopic crack-resistant fiber is a coarse polypropylene fiber with a diameter of 0.3-0.5 mm and a length of 18-24 mm; and the microscopic toughening fiber is a high-modulus PE or POM ultrafine fiber with a diameter of 10-50 μm and a length of 6-12 mm.
[0062] Optionally, the water reduction rate of the viscosity-reducing polycarboxylate superplasticizer is ≥40%; the internal curing agent is pre-absorbent lightweight aggregate or pre-absorbent saturated superabsorbent polymer (SAP).
[0063] like Figure 1 As shown, a method for preparing high-strength fiber-reinforced concrete is described, wherein any of the above-mentioned high-strength fiber-reinforced concretes is prepared, and the preparation method is as follows:
[0064] The micro-toughening fibers are dry-mixed with 40% of the total amount of cementitious materials and all fine aggregates to form a dispersion.
[0065] Add coarse aggregate, dispersed material, macroscopic reinforcing fiber and fine crack-resistant fiber to the mixer and dry mix for 60-90 seconds;
[0066] Add the remaining cementitious material and 60% of the total water volume of water, stir for 90 seconds to obtain a slurry;
[0067] Add the remaining water, viscosity-reducing polycarboxylate superplasticizer and internal curing agent, and stir for ≥240s until the slurry spread is ≥650mm.
[0068] The grout is poured into shape and compacted using either high-frequency, vibration-free or low-frequency, large-amplitude vibration.
[0069] After pouring, initial covering and water retention curing are carried out; after water retention curing is completed, steam curing is carried out, with the temperature increased at 15℃ / h to the maximum temperature, the maximum temperature ≤60℃, and the temperature is kept constant for 6-8 hours, then the temperature is decreased at 10℃ / h; after demolding, wet curing or sealed curing is carried out for ≥14 days.
[0070] A wind power hybrid tower transition section is prepared using the above-mentioned high-strength fiber concrete preparation method.
[0071] Example 1
[0072] A high-strength fiber-reinforced concrete has the following raw material proportions (kg / m³): 370 kg of 52.5 grade low-alkali silicate cement, 30 kg of silica fume, 155 kg of S105 grade ultrafine mineral powder, 30 kg of ultrafine fly ash, and 15 kg of composite crack-resistant agent; 1050 kg of coarse aggregate and 640 kg of fine aggregate manufactured sand; 20 kg of macroscopic reinforcing steel fiber, 4.5 kg of microscopic crack-resistant polypropylene coarse fiber, and 0.9 kg of microscopic toughening PE ultrafine fiber; 14 kg of viscosity-reducing polycarboxylate high-performance water-reducing agent, 1.5 kg of internal curing agent, and 108 kg of water (the mass ratio of water to cementitious materials is 0.18). Preparation process: Micro-toughening fibers are dry-mixed with 40% of the total cementitious material and all fine aggregates to form a dispersion. Coarse aggregates, dispersions, macro-reinforcing fibers, and micro-crack-resistant fibers are added to a mixer and dry-mixed for 60 seconds. The remaining cementitious material and 60% of the total water volume are added and mixed for 90 seconds to obtain a slurry. The remaining water, viscosity-reducing polycarboxylate superplasticizer, and internal curing agent are added and forcibly mixed for 240 seconds until the slurry spread is ≥650mm. The slurry is then cast into shape. After casting, initial covering and water-retaining curing are performed. After water-retaining curing, steam curing is performed, with the temperature increased at 15℃ / h to a maximum of 60℃, held at that temperature for 6 hours, and then decreased at 10℃ / h. After demolding, wet curing or sealed curing is performed for 14 days.
[0073] Example 2
[0074] A high-strength fiber-reinforced concrete has the following raw material proportions (kg / m³): 360 kg of 52.5 grade low-alkali silicate cement, 28 kg of silica fume, 152 kg of S105 grade ultrafine mineral powder, 32 kg of ultrafine fly ash, and 18 kg of magnesium-based crack-resistant agent; 1100 kg of coarse aggregate and 600 kg of fine aggregate manufactured sand; 15 kg of macroscopic reinforcing steel fiber, 3 kg of microscopic crack-resistant polypropylene coarse fiber, and 0.6 kg of microscopic toughening PE ultrafine fiber; 11 kg of viscosity-reducing polycarboxylate high-performance water-reducing agent, 2.5 kg of internal curing agent, and 112.1 kg of water (water to cementitious material mass ratio is 0.19). The preparation method is the same as in Example 1.
[0075] Example 3
[0076] A high-strength fiber-reinforced concrete has the following raw material proportions (kg / m³): 375 kg of 52.5 grade low-alkali silicate cement, 32 kg of silica fume, 158 kg of S105 grade ultrafine mineral powder, 28 kg of ultrafine fly ash, 6 kg of magnesium-based crack-resistant agent, and 6 kg of composite crack-resistant agent; 1000 kg of coarse aggregate and 680 kg of fine aggregate manufactured sand; 5 kg of macroscopic reinforcing steel fiber, 6 kg of microscopic crack-resistant polypropylene coarse fiber, and 1.2 kg of microscopic toughening fiber POM ultrafine fiber; 18 kg of viscosity-reducing polycarboxylate high-performance water-reducing agent, 4 kg of internal curing agent, and 102.85 kg of water (water to cementitious material mass ratio is 0.17). The preparation method is the same as in Example 1.
[0077] Comparative Example 1
[0078] The standard C90 concrete has the following raw material mix proportions (kg / m³): cement 375, silica fume 32, mineral powder 158, ultrafine fly ash 28, composite crack-resistant agent 12; coarse aggregate 1000, manufactured sand 680; water-reducing agent 18, water (water-cement ratio 0.17).
[0079] Comparative Example 2
[0080] The raw material mix ratio (kg / m³) for C90 concrete with single steel fiber admixture is as follows: cement 360, silica fume 28, mineral powder 152, ultrafine fly ash 32; steel fiber 40; coarse aggregate 1100, manufactured sand 600; water-reducing agent 11, water (water-binder ratio 0.19).
[0081] The high-strength fiber-reinforced concretes prepared in Examples 1-3 and Comparative Examples 1-2 were tested according to relevant standards such as industry standard JGJ / T 283-2012 "Technical Specification for Application of Self-Compacting Concrete" and national standard GB / T 50081-2019 "Standard for Test Methods of Physical and Mechanical Properties of Concrete". The test results are shown in Tables 1 and 2.
[0082] Table 1 Relevant experimental results
[0083] Table 2 Early crack resistance
[0084]
[0085] As shown in Tables 1 and 2, Examples 1-3 all exhibited excellent comprehensive performance. Notably, Example 3, with its lower macroscopic steel fiber content (5 kg / m³), had the smallest early cracking area (80 mm² / m²), indicating that the suppression of early plastic shrinkage cracks mainly relied on the dense network of microscopic polypropylene and microscopic POM fibers. In contrast, Example 1, with its higher macroscopic steel fiber content (20 kg / m³), achieved the highest 28-day splitting tensile strength (7.6 MPa), demonstrating that macroscopic steel fibers played a decisive role in resisting structural loads and increasing the ultimate tensile strength in the later stages of concrete hardening. Each component performed its specific function, achieving full-cycle crack resistance and toughening.
[0086] Combination Figures 2 to 5 The mechanical property tests show that the high-strength fiber-reinforced concrete prepared in the embodiments of the present invention exhibits good performance in compressive strength tests (such as...). Figure 2 , Figure 3 (as shown) and splitting test (as shown) Figure 4 , Figure 5 As shown, when the ultimate load was reached, none of the specimens exhibited the brittle spalling phenomenon commonly seen in ordinary ultra-high strength concrete. The multi-scale hybrid fibers on the failure surface played a significant bridging and crack-preventing role, enabling the concrete to maintain a good overall shape (cracked but not disintegrated) after failure, fully demonstrating the excellent effect of the formulation of this invention in improving the flexural toughness and fatigue resistance of concrete.
[0087] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the protection scope of the present invention.
Claims
1. A high-strength fiber-reinforced concrete, characterized in that, By weight, it includes the following components: 350-380 parts of 52.5 grade low-alkali silicate cement; Silica fume: 25-35 parts; S105 grade ultrafine mineral powder: 100-160 parts; Ultrafine fly ash or metakaolin: 25-35 parts; Crack-resistant agent: 10-20 parts; Coarse aggregate: 1000-1100 parts; Fine aggregate: 600-680 parts; Macroscopic reinforcing fiber: 5-25 parts; Microscopic crack-resistant fibers: 3-6 parts; Micro-toughening fibers: 0.6-1.2 parts; Viscosity-reducing polycarboxylate high-performance water-reducing agent: 11-18 parts; Internal conditioner: 1.5-4 parts; Water: 90-115 parts; The 52.5 grade low-alkali silicate cement, silica fume, S105 grade ultrafine mineral powder, ultrafine fly ash or metakaolin, and the crack-resistant agent together constitute the cementitious material, and the mass ratio of water to the cementitious material is 0.14-0.
23.
2. The high-strength fiber-reinforced concrete according to claim 1, characterized in that, The crack-resistant agent is a composite crack-resistant agent, a magnesium-based crack-resistant agent, or a mixture of a composite crack-resistant agent and a magnesium-based crack-resistant agent; the composite crack-resistant agent is composed of a light-burned magnesium oxide expansion source and a shrinkage-reducing component mixed at a mass ratio of 6:4; the magnesium oxide content of the light-burned magnesium oxide expansion source is ≥95%; the shrinkage-reducing component is a powder shrinkage-reducing agent.
3. The high-strength fiber-reinforced concrete according to claim 1, characterized in that, The coarse aggregate is high-strength granite or basalt crushed stone with a particle size of 5-12mm or 5-16mm, and the content of needle-like and flaky particles in the coarse aggregate is ≤3%, and the crushing index is ≤8%; the fine aggregate is manufactured sand with a methylene blue value (MB) ≤0.8, a stone powder content of 6-9%, and has undergone three-stage gradation optimization.
4. The high-strength fiber-reinforced concrete according to claim 1, characterized in that, The macroscopic reinforcing fibers are hook-shaped or wavy steel fibers with a length of 30-35 mm and an aspect ratio of 50-70; the microscopic crack-resistant fibers are coarse polypropylene fibers with a diameter of 0.3-0.5 mm and a length of 18-24 mm; the microscopic toughening fibers are high-modulus PE or POM ultrafine fibers with a diameter of 10-50 μm and a length of 6-12 mm.
5. The high-strength fiber-reinforced concrete according to claim 1, characterized in that, The water reduction rate of the viscosity-reducing polycarboxylate high-performance water-reducing agent is ≥40%; the internal curing agent is pre-absorbent lightweight aggregate or pre-absorbent saturated superabsorbent polymer (SAP).
6. A method for preparing high-strength fiber-reinforced concrete, characterized in that, The high-strength fiber-reinforced concrete according to any one of claims 1-5 is prepared by the following method: The micro-toughening fibers are dry-mixed with 40% of the total amount of cementitious materials and all fine aggregates to form a dispersion. Add the coarse aggregate, the dispersed material, the macroscopic reinforcing fiber, and the fine crack-resistant fiber to the mixer and dry mix for 60-90 seconds; Add the remaining cementitious material and 60% of the total water volume of water, stir for 90 seconds to obtain a slurry; Add the remaining water, viscosity-reducing polycarboxylate superplasticizer and internal curing agent, and force stir for ≥240s until the spread of the slurry is ≥650mm; The slurry is cast into shape and compacted using either high-frequency, vibration-free or low-frequency, large-amplitude vibration. After pouring, initial covering and water retention curing are carried out; after water retention curing is completed, steam curing is carried out, with the temperature increased at 15℃ / h to the maximum temperature, the maximum temperature being ≤60℃, and the temperature is maintained for 6-8 hours, followed by cooling down at 10℃ / h; after demolding, wet curing or sealed curing is carried out for ≥14 days.
7. A wind power hybrid tower transition section, characterized in that, It is prepared using the high-strength fiber concrete preparation method described in claim 6.